A Rigorous Calculation Method for Determining Potential-pH Diagrams in Metal-ammoniawater Systems - Salhi, Ramdane; Eddine Bouhidel, Kamel (Asian Journal of Chemistry, 2016)
The main aim of this research work is to determine optimal leaching conditions: Eh, pH and total ammonia concentrations, for recovery of copper and nickel from electroplating hydroxide sludges containing iron, chrome, copper and nickel hydroxides. This has been preceded by a theoretical approach and numerical and computer calculation. By maintaining total dissolved metal and total ammonia constant, all equilibriums are taken into consideration simultaneously. The diagrams then show stable domains for the solution and solids. Solubility curves and potential-pH diagrams for the copper-water-ammonia and nickel-water-ammonia systems at different total metal and different total ammonia concentrations have been presented. This analysis has practical value in interpreting the process conditions required to conduct hydrometallurgical process.